The Political Divide Between Lay and Elite Atheism - Cimino, Richard P. (Secularism and Nonreligion, 2020)
A long-standing debate in atheist and secular humanist circles has been whether organized secularists should embrace a broader political agenda or steer clear of such commitments. The latter camp argues that atheism does not include a set of socio-political markers that sets it off from other movements; it is mainly a science- and reason-based philosophy challenging belief in the supernatural that can be adapted to a wide range of political orientations. We find this view increasingly reflected among both atheist and secular humanist leaders and publications, especially in the “new atheist” movement, which has drawn high proportions of atheists interested in science. In this paper, we will examine the political discourse and views of atheist leaders and opinion-makers and those of members of atheist-secular humanist organizations during and after the 2016 elections. We conduct a textual analysis of secularist publications and web sites as well as use a survey we conducted among 3,000 members of a prominent atheist organization to understand the political divide in American secularism and the prospects for greater unity in this diffuse movement.